Odpowiedzi

2010-02-08T19:51:53+01:00
A). = 2x²-10x-3x²+6x+x²-2x = -6x
b). = a²+ab+ac-ba+b²-bc-ca+cb+c²
c). = x³+2x²+x+4x³+8x²-6:2 = 5x³+10x²+x-3

;))
Najlepsza Odpowiedź!
2010-02-08T19:54:01+01:00
A) 2x(x-5)-3(x² -2x)+(x-2)x=2x²-10x-3x²+6x+x²-2x=-6x

B) a(a+b+c)-b(a-b+c)-c(a-b-c)=a²+ab+ac-ab+b²-bc-ac+bc+c²=a²+b²+c²

C) x(x²+2x+1)-(-4³+8x²-6):2=x³+2x²+x-(-2x³+4x²-3)=x³+2x²+x+2x³-4x²+3=3x³-2x²+x-3

Mam nadzieję, ze pomogłam :)
2010-02-08T19:54:10+01:00
2x²-10x-3x²+6x+x²-2x=-6x

a²+ab+ac -ba+b²-bc-ca+cb+c²=a²+c²+b²

x³+2x²+x+2x³+4x³+3=3+x+7x³+2x²